2023
DOI: 10.3389/fphar.2023.1143969
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and mechanism of vonoprazan-containing triple therapy in the eradication of Helicobacter pylori

Abstract: Purpose: Vonoprazan (VPZ) produces a strong acid-inhibitory effect, which can potentially eradicate Helicobacter Pylori (H. pylori). We aimed to assess whether a 14-day VPZ-containing triple therapy was safe and effective in the Chinese population and the potential mechanism.Methods: Enrolled patients confirmed to be infected with H. pylori were randomly divided into four groups: VPZ + doxycycline + furazolidone, VPZ + doxycycline + amoxicillin, esomeprazole (EPZ) + bismuth + doxycycline + furazolidone, and EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…A regressive study 19 that performed a propensity score‐matched analysis provides a level of evidence comparable to that of RCTs. Eight studies 18–22,24–26 were included in the PP analysis, and the results were consistent with those of the ITT analysis (shown in Figure 3). Particularly, the ERs of VPZ‐based regimens and PPIs‐based regimens (BQT) were 94.80% and 89.88%, respectively (OR = 2.25, 95% CI (1.37, 3.69), p = 0.001 < 0.05, shown in Figure 3).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…A regressive study 19 that performed a propensity score‐matched analysis provides a level of evidence comparable to that of RCTs. Eight studies 18–22,24–26 were included in the PP analysis, and the results were consistent with those of the ITT analysis (shown in Figure 3). Particularly, the ERs of VPZ‐based regimens and PPIs‐based regimens (BQT) were 94.80% and 89.88%, respectively (OR = 2.25, 95% CI (1.37, 3.69), p = 0.001 < 0.05, shown in Figure 3).…”
Section: Resultssupporting
confidence: 55%
“…A total of 568 studies were obtained, and after eliminating duplicates and systematic evaluations, and reading their abstracts and entire text, a total of 10 18–27 studies were finally included (shown in Figure 1). Out of the 10 studies, one was NRCT 19 and nine were RCTs, 18,20–27 and all studies were conducted in China. A total of 2587 patients 15 were included; 1452 of them were in the VPZ‐based group, whereas 1135 of them were in the BQT group.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 RCTs were included, 15 , 16 , 22 39 involving 5815 patients with Hp infection, with 3153 patients in the treatment group, and 2662 patients in the control group. The basic characteristics of the included studies are shown in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the recent interest in H. pylori infection and management, biofilms are still quite understudied. Little information is available about the mechanisms involved in antibiotic tolerance and resistance (Hathroubi et al 2020b ; Zhang et al 2023 ). Multiple techniques, including genomic, proteomic, transcriptomic, and target-specific investigations, have been employed to determine the factors affecting biofilm formation.…”
Section: Introductionmentioning
confidence: 99%